(untitled) (Annals of Medical Research, 2021)
Aim: To develop and validate a survey for the measurement of the effect of contact lenses on ocular physiological parameters, visual functions, appearance, and socioeconomic and psychological factors.Material and Methods: Between September 2018and July 2019, 392 participants who applied to Erzincan University Faculty of Medicine Department of Ophthalmology were included in the study. All patients were contact lens users at least one year. Participants were aged 18 or above. A questionnaire containing 36 questions was created and distributed to contact lens users. All participants answered the questionnaire completely.Results: Of the 392 respondents, 202 (51.5%) were male and 190 (48.5%) were female. The total scores of correlations of 36 items ranged from 0.310 to 0.598. Factor loads ranged from 0.359 to 0.770 and all were considered statistically significant. (KMO: 0.878 p0.001) The questionnaire was divided into three subgroups: ocular and visual effects, appearance and socioeconomic and psychological factors. Cronbach’s α for the correlation of items within the three subscales were 0.927 for ocular and visual effects, 0.929 for appearance and 0.892 for socioeconomic and psychological factors subscale and this show the survey is reliable. Conclusion: The contact lens satisfaction survey was meticulously developed using both exploratory factor analysis and Rasch analysis to assure good content validity, internal consistency, and a low answering load. Our contact lens satisfaction survey can be used for contact lens users aged 18 years and above who have been using contact lenses for at least 1 year.